Stabilization of Cu7 clusters in azide networks: syntheses, structures and magnetic behaviour. Issue 12 (17th February 2016) - Mistry, Subhradeep; Sutter, Jean-Pascal; Natarajan, Srinivasan
Abstract : Two Cu II azide compounds having Cu7 clusters have been prepared, by employing two different blocking amines with different denticities, and their magnetic behaviour is described and discussed. Abstract : Two new azide bridged copper(ii ) coordination polymer compounds, [Cu7 (N3 )14 (C3 H10 N2 )(C4 H13 N3 )] n (I ) and [Cu7 (N3 )14 (C3 H10 N2 )(C5 H15 N3 )2 ] n (II ) [where C3 H10 N2 = 1, 2-diaminopropane (1, 2-DAP); C4 H13 N3 = diethylenetriamine (DETA); C5 H15 N3 = N -2-aminoethyl-1, 3-propanediamine (AEDAP)] were prepared by employing a room temperature diffusion technique involving three layers. Single crystal studies reveal that both compoundsI andII, have similar connectivity forming Cu7 clusters through end-on (EO) bonding of the azide. The Cu7 clusters are connected through end-to-end (EE) connectivity of the azides forming three-dimensional structures. Magnetic studies confirmed the ferromagnetic interactions within the Cu7 units and revealed the occurrence of concomitant ferro- and antiferro-magnetic interactions between these clusters. As a resultI behaves as a weak-ferromagnet with T C = 10 K.